Loading direction dependence of asymmetric response of <c+a> pyramidal slip in rolled AZ31 magnesium alloy - Yuzhi Zhu; Dewen Hou; Kaixuan Chen; Zidong Wang (Journal of Magnesium and Alloys, 2023)
Textured magnesium alloys usually exhibit anisotropic mechanical behavior due to the asymmetric activation of different twinning and slipping modes. This work focuses on the <c+a> pyramidal slip responses of rolled AZ31 magnesium alloy under two loading conditions, compressive and tensile loading along the normal direction. Under the condition where the compressive loading direction is closely parallel to the c-axis of the unit cell, tensile twinning and basal slips are prohibited, <c+a> dislocations then active and tend to accumulate at grain boundaries and form dislocation walls. Meanwhile, these dislocations exhibit zigzag morphologies, which result from the cross-slip from {101¯1} first-order pyramidal plane to {112¯2} second-order pyramidal plane, then back to {101¯1} first-order pyramidal plane. Under the condition where tensile twins are prevalent, {101¯1} first-order and {112¯2} second-order pyramidal dislocations are favorable to be activated. Both types of dislocations behave climb-like dissociations onto the basal plane, forming zigzag dislocations.